ABO Genotype and Risk of Thrombotic Events and Hemorrhagic Stroke - Wiggins, KL (2008)
BACKGROUND: The non-O alleles of the ABO genotype have been associated with an increased risk of thrombosis. Risk associated with the specific A(1), A(2), or B alleles is not well defined. OBJECTIVES: To examine the association of ABO genotype with myocardial infarction (MI), ischemic stroke, hemorrhagic stroke, and venous thrombosis (VT). PATIENTS/METHODS: We used data from 2 ongoing population-based case-control studies of MI, stroke, and VT. Cases included hypertensive adults and post-menopausal women with incident non-fatal MI (n=1063), ischemic stroke (n=469), and hemorrhagic stroke (n=91), and postmenopausal women with incident non-fatal VT (n=504). Controls were frequency matched to cases on age, sex, hypertension status, and year of identification. ABO genotypes were determined using single nucleotide polymorphisms and subjects were grouped by diplotype according to the presence of O(1), O(2), A(11), A(2), and B alleles. Logistic regression was used to test the association of diplotypes with risk of each outcome. RESULTS: Compared with the O(1)O(1) group, the A(11) allele was associated with an increased risk of VT (odds ratio [OR] 1.79, 95% confidence interval: 1.41–2.26) and MI (OR 1.23 [1.05–1.44]). The B allele was associated with an increased risk of VT (OR 1.82 [1.29–2.57]) and ischemic stroke (OR 1.59 [1.17–2.17]). The AB diplotype category was associated with a 2.7-fold risk of VT (OR 2.70 [1.73–4.21]). No other associations reached significance. CONCLUSIONS: The VT and MI findings are confirmatory and the ischemic stroke finding with the B allele is a novel and needs replication.